2023
DOI: 10.1021/acs.jmedchem.3c00108
|View full text |Cite
|
Sign up to set email alerts
|

Going beyond Binary: Rapid Identification of Protein–Protein Interaction Modulators Using a Multifragment Kinetic Target-Guided Synthesis Approach

Abstract: Kinetic target-guided synthesis (KTGS) is a powerful screening approach that enables identification of small molecule modulators for biomolecules. While many KTGS variants have emerged, a majority of the examples suffer from limited throughput and a poor signal/noise ratio, hampering reliable hit detection. Herein, we present our optimized multifragment KTGS screening strategy that tackles these limitations. This approach utilizes selected reaction monitoring liquid chromatography tandem mass spectrometry for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…(Figure S1) The thio acids were prepared as fluorenylmethyl thioesters from corresponding carboxylic acids, then subsequently deprotected with 5% DBU in situ prior to carrying out the templation experiments; as previously described . Carboxylic acids and sulfonyl azides used in this study were either commercially available or synthesized as previously reported . The investigation of Nf Glck-templated N -acylsulfonamide ( SZTA ) formation commenced with the incubation of fragments in a multicombinatorial fashion in the presence and absence of the parasitic enzyme.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Figure S1) The thio acids were prepared as fluorenylmethyl thioesters from corresponding carboxylic acids, then subsequently deprotected with 5% DBU in situ prior to carrying out the templation experiments; as previously described . Carboxylic acids and sulfonyl azides used in this study were either commercially available or synthesized as previously reported . The investigation of Nf Glck-templated N -acylsulfonamide ( SZTA ) formation commenced with the incubation of fragments in a multicombinatorial fashion in the presence and absence of the parasitic enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the fragments used in this study may help to explain these findings. Our library was initially curated to target Bcl-X L and thus was designed to bind the large, hydrophobic interfaces found in protein–protein interactions. ,, Expansion of this library to target another PPI, Mcl-1, has unsurprisingly led to a larger, more hydrophobic fragment library than would be expected for targeting enzymes . This is exemplified by average c Log P and MW values of 6.3 and 606 Da, respectively, for the 12 compounds.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations